The Influence of Fuel Prices and Unemployment Rate towards the Poverty Level in Indonesia - Muthalib, Abd Azis; Adam, Pasrun; Rostin, Rostin; Saenong, Zainuddin; Suriadi, La Ode (International Journal of Energy Economics and Policy, 2018)
The purpose of this study is to examine the influence of fuel prices and unemployment rates toward poverty levels. The data used were yearly time series data consisting of fuel price, unemployment rate, and poverty level that span from 1998 to 2017. To test the influence of fuel price and unemployment rate toward the poverty level, the autoregressive distributed lag (ARDL) model was used. . The results of data analysis showed that in the short-term, there is a negative influence of fuel prices toward the level of poverty. Meanwhile, there is a positive influence of unemployment rate on poverty level in the long-term. In this case, every 1% increase (decrease) the unemployment rate, the poverty rate rose (down) by 33.09%. Keywords: Fuel price, unemployement rate, poverty level, and ARDL model. JEL Calassifications: C220, E310, I32, J64.